Kualitas Pelayanan Program Keluarga Berencana pada Dinas Pengendalian Penduduk dan Keluarga Berencana di Kabupaten Kepulauan Sula - Umaternate, Saleha; Hafel, Muhlis; Arifin, M. Husni (Universitas Islam Tribakti Lirboyo Kediri, 2024)
This study aims to evaluate the quality of services provided by the Family Planning and Population Control Office in Kepulauan Sula Regency in implementing the Family Planning Program. The program is designed to control population growth rates and to establish healthy, happy, and prosperous families. The research employs a qualitative descriptive method to explore and understand field phenomena through in-depth qualitative data collection. The findings indicate that the targets of the Family Planning Program in Kepulauan Sula Regency are categorized into two groups: direct and indirect targets. Direct targets include Couples of Childbearing Age (CBA) spread across 12 sub-districts, with the objective of reducing birth rates through effective and sustainable contraceptive use. Indirect targets involve program implementers and managers, aiming to lower birth rates through an integrated population policy approach. These findings have theoretical implications for understanding how population policies and family planning programs can be optimized to achieve the goal of quality family development, particularly in remote areas like Kepulauan Sula Regency.